Green management: intervention strategy on job burnout and performance improvement in terms of employee tenure - Hidayat, Arif (Enrichment : Journal of Management, 2023)
Job burnout is a response to stressful situations, difficult to control, and conditions that affect employee performance. Green Management as a business strategy is shown in the form of respect for the environment and corporate cultural values. So the purpose of this study is to examine the effect of tenure on job output and employee performance that is intervened by the green management strategy. This study selected employees with more than five and more than ten years of service who were indicated to be experiencing job burnout. Job evaluation document data and competency gaps found conditions of job burnout and decreased performance. The data were analyzed in inferential statistics. The results show a significant effect of tenure on job burnout; tenure intervened by the green management strategy has a significant effect on job burnout; tenure intervened by the green management strategy affects employee performance. The green management strategy has a negative effect on job burnout, the green management strategy has a significant effect on employee performance, and job burnout has a negative effect on employee performance.